An analysis of the effect of organisational capacity on organisational performance in project implementation : case of the Organisation of Rural Associations for Progress (ORAP) - Rankonyana, Lawrence (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPA)--Stellenbosch University, 2015.